Volcanological and geothermal records observations - Philippines. Commission on Volcanology (Quezon City The Commission, 1975)
Annual.
Under the auspices of the National Science Development Board and Commission on Volcanology.
Keywords: Volcanoes -- Philippines; Geothermal resources -- Philippines; Volcanic activity prediction; Volcanological research -- Philippines